Do Anabolic Androgenic Steroids Really Cause Harm? A Comprehensive Examination of Adverse Effects - Paweł Siudziński; Mateusz Łyko; Alicja Skoczylas; Jakub Kurasz; Wojciech Maj; Wiktoria Tomaszewska; Wiktoria Podlasiewicz; Katarzyna Pala; Piotr Dudziak; Anna Nowak; Maria Golińska (Quality in Sport)
Anabolic steroids, synthetic derivatives of testosterone, are frequently employed in clinical settings to address hormonal deficiencies and, controversially, in athletic contexts to augment physical performance. These compounds exert their physiological effects by activating androgen receptors, thereby stimulating protein synthesis, promoting muscle hypertrophy, and accelerating tissue regeneration. These processes are mediated through the modulation of insulin-like growth factor-1 (IGF-1) and the inhibition of glucocorticoid-induced catabolism. However, the unsupervised and excessive use of anabolic steroids, often motivated by the pursuit of rapid aesthetic or performance enhancement, is associated with a myriad of adverse health outcomes. Such complications encompass damage to the reproductive system, renal dysfunction, hepatotoxicity, cardiovascular pathology, and neuropsychiatric disturbances. Given their substantial potential for misuse, anabolic steroids are stringently regulated, necessitating that healthcare professionals remain astutely aware of their adverse effects to ensure timely recognition and intervention.